Molecular Approaches for High Throughput Detection and Quantification of Genetically Modified Crops: A Review - Salisu, Ibrahim B.; Shahid, Ahmad A.; Yaqoob, Amina; Ali, Qurban; Bajwa, Kamran S.; Rao, Abdul Q.; Husnain, Tayyab (Frontiers in Plant Science, 2017)
As long as the genetically modified crops are gaining attention globally, their proper approval and commercialization need accurate and reliable diagnostic methods for the transgenic content. These diagnostic techniques are mainly divided into two major groups i.e. Identification of transgenic (1) DNA and (2) proteins from GMOs and their products. Conventional methods such as PCR (Polymerase chain reaction) and enzyme-linked immunosorbent assay (ELISA) were routinely employed for DNA and protein based quantification respectively. Although, these Techniques (PCR & ELISA) are considered as significantly convenient and productive, but there is need for more advance technologies that allow for high throughput detection and the quantification of GM event as the production of more complex GMO is increasing day by day. Therefore, recent approaches like Microarray, capillary gel electrophoresis (CGE), digital PCR and next generation sequencing are more promising due to their accuracy and precise detection of transgenic contents. The present article is a brief comparative study of all such detection techniques on the basis of their advent, feasibility, accuracy and cost effectiveness. However, these emerging technologies have a lot to do with detection of a specific event, contamination of different events and determination of fusion as well as stacked gene protein are the critical issues to be addressed in future.